The paths of migration of charcoal particles in the post-pyrogenic soils of the taiga and tundra depending on features of fire and environmental factors - D. G. Petrov (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The work is devoted to the analysis of the regularities of the movement of charcoal particles in the ecosystems of the middle taiga, northern taiga and southern tundra experiencing the influence of fires. Since coniferous vegetation is subjected to intense combustion, fires often lead to cyclical changes in the vegetation cover. The process of burning leads to the forest litter damage, making the soil cover vulnerable to erosion. Intense fires affect the amount of pyrogenic material that can be stored for thousands of years under favorable conditions. The aim of the research was to estimate the influence of environmental factors on the use of carbonaceous particles in modern time series (from 1 to 119 years). The features of soils (particle size distribution, moisture content), relief features (presence of depressions), the effect of precipitation material after a fire, as well as features of combustible litter were considered. On the territory of the middle and northern taiga, in the Pechora-Ilychsky and Pinezhsky reserves, textural-differentiated and alpha-humus soils are considered. On the territory of the southern tundra, in the area of the settlement Zapolyarny, peat-gley soils are considered. It was revealed that the migration of coal to the depth of the soil profile depends to the greatest extent on the particle size distribution – for example, in more sandy soils, coals are scattered throughout the profile, and in clay soils they are concentrated above the first fine-textured horizon. The nature of the coals determines their shape and size, which depend on the type of burnt plant community. Communities with a scattered stand, dominated by lichens in the moss-lichen cover, burn with the formation of microparticles of coal or dispersed carbonaceous particles that easily move along the soil profile (up to the depth of 80 cm). Plant communities with more tree species in their composition, during combustion form large carbonaceous particles, which are often present in the newly formed litter. Charcoal migration is influenced by both the climatic zone and post-pyrogenic erosion. Thus, depending on the variety of environmental conditions, the speed and volume of movement of carbonaceous particles change significantly both when comparing different natural zones and within one zone. Four schemes have been developed for the motion of charcoal along the profile over time: uniformly diffused, unevenly diffused, barrier and turbation.